2018
DOI: 10.1084/jem.20172335
|View full text |Cite
|
Sign up to set email alerts
|

Effector CD4 T cells with progenitor potential mediate chronic intestinal inflammation

Abstract: Dysregulated CD4 T cell responses are causally linked to autoimmune and chronic inflammatory disorders, yet the cellular attributes responsible for maintaining the disease remain poorly understood. Herein, we identify a discrete population of effector CD4 T cells that is able to both sustain and confer intestinal inflammation. This subset of pathogenic CD4 T cells possesses a unique gene signature consistent with self-renewing T cells and hematopoietic progenitor cells, exhibits enhanced survival, and continua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 45 publications
(67 reference statements)
0
22
0
Order By: Relevance
“…However, the sialidase used in these prior studies cleaves both α2–3 and α2–6 sialic acids, which may not be biologically equivalent to selective changes in α2–6 sialylation induced by alterations in ST6Gal-I expression. Fluctuations in ST6Gal-I levels are biologically relevant, in that ST6Gal-I expression is dynamically regulated in certain immune cell populations [ 3 , 39 , 40 ], and typically upregulated in epithelial malignancies [ 41 , 42 ]. Moreover, another group utilized a sialidase specific for α2–3 sialic acids, along with lectins that block either α2–3 or α2–6 sialic acids, and determined that it was the α2–3, but not α2–6, sialic acids that hindered TLR4 receptor activation and signaling [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the sialidase used in these prior studies cleaves both α2–3 and α2–6 sialic acids, which may not be biologically equivalent to selective changes in α2–6 sialylation induced by alterations in ST6Gal-I expression. Fluctuations in ST6Gal-I levels are biologically relevant, in that ST6Gal-I expression is dynamically regulated in certain immune cell populations [ 3 , 39 , 40 ], and typically upregulated in epithelial malignancies [ 41 , 42 ]. Moreover, another group utilized a sialidase specific for α2–3 sialic acids, along with lectins that block either α2–3 or α2–6 sialic acids, and determined that it was the α2–3, but not α2–6, sialic acids that hindered TLR4 receptor activation and signaling [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, a highly pathogenic subset of stem-like CD4 T cells was identified in a mouse model of colitis. Significantly, these T cells have enriched ST6Gal-I and are also resistant to apoptosis [ 39 ]. Many of these aforementioned studies indicate that ST6Gal-I is vital for immune cell differentiation and/or activation, suggesting that ST6Gal-I regulates immune cell fate.…”
Section: Discussionmentioning
confidence: 99%
“…[138][139][140] Long-lived T H 17 cells with stem cell-like attributes of self-renewal and multipotency were also found. 141 Interest in stem-like T helper cells has recently increased by reports of their involvement in autoimmune diseases, including chronic colitis 142 and experimental autoimmune encephalomyelitis. 132 The functional identification of these cells has revealed another dimension in T helper cell differentiation that is only decipherable under specific disease contexts but is physiologically relevant.…”
Section: T-cell Plasticity and Heterogeneitymentioning
confidence: 99%
“…CD4 + T cells mainly contain effector CD4 + T cells such as T helper 1 (Th1), Th2, Th17, and regulatory T cells (Tregs). Studies have shown that intestinal immune homeostasis depends on the regulation and balance of these CD4 + T cell subgroups, and the deregulated overexpansion and activation of Th1 and Th17 cells in relation to Tregs can lead to intestinal inflammation, such as IBD [1012]. Since Th1 and Th17 cells could secrete large amounts of proinflammatory cytokines such as IFN- γ , TNF- α , IL-1 β , and IL-17, resulting in persistent intestinal inflammation [13], medications that can suppress colonic oxidative status and inhibit Th1/Th17 responses would be shown to be clinically effective.…”
Section: Introductionmentioning
confidence: 99%